The Effect of Individuals Asymptomatic (Carrier) on The Dynamical Behavior Of a COVID-19 Virus - AL-Husseiny, Hassan F.; Mohsen, Ahmed A.; Zhou, Xueyong (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, a novel coronavirus (COVID-19) model is proposed and investigated. In fact, the pandemic spread through a close contact between infected people and other people but sometimes the infected people could show two cases; the first is symptomatic and the other is asymptomatic (carrier) as the source of the risk. The outbreak of Covid-19 virus is described by a mathematical model dividing the population into four classes. The first class represents the susceptible people who are unaware of the disease. The second class refers to the susceptible people who are aware of the epidemic by media coverage. The third class is the carrier individuals (asymptomatic) and the fourth class represents the infected individuals. The existence, uniqueness and bounded-ness of the solutions of the model are discussed. All possible equilibrium points are determined. The locally asymptotically stable of the model is studied. Suitable Lyapunov functions are used to investigate the globally asymptotical stability of the model. Finally, numerical simulation is carried out to confirm the analytical results and to understand the effect of varying the parameters of how the disease spreads.